Nutritional and Antioxidant Valorization of Grape Pomace from Argentinian Vino De La Costa and Italian Cabernet Wines - Luciano M. Guardianelli; María V. Salinas; María C. Puppo; Alyssa Hidalgo; Gabriella Pasini (Foods)
Wine production generates by-products that require proper management and reuse to minimize their environmental impact. Grape pomace, a by-product of winemaking, holds significant nutritional and bioactive potential. This study evaluated the nutritional and antioxidant profiles of pomace from Isabella grapes (La Plata, Argentina) and Cabernet grapes (Veneto, Italy). Both varieties contain high levels of dietary fiber, especially Cabernet. However, Cabernet showed lower protein and lipid levels than Isabella. Calcium, potassium, and phosphorus were the major minerals in both by-products. Isabella exhibited a higher content of essential polyunsaturated fatty acids, particularly α-linoleic acid, while Cabernet shows a greater proportion of saturated and monounsaturated fatty acids. Additionally, Isabella exhibited significantly higher levels of caffeic acid derivatives (506.4 vs. 38.2 mg/kg dry weight), catechin (1613.2 vs. 294.8 mg/kg dry weight), epicatechin (1229.2 vs. 230.3 mg/kg dry weight), and total anthocyanins (2649 vs. 607.5 mg kuromanin/kg dry weight), as well as a greater total polyphenol content and antioxidant activity compared to Cabernet. These results highlight grape pomace’s potential as a valuable functional ingredient.